State-of-technology review of water-based closed seasonal thermal energy storage systems. (October 2019) - Bott, Christoph; Dressel, Ingo; Bayer, Peter
Abstract: Continuous use of fluctuating renewable energy resources is facilitated only by temporal storage solutions. For long-term and seasonal heat storage, many large-scale closed seasonal thermal energy storages (TES) have been built in the recent decades. Still there is no consistent picture available that contrasts the different technologies and summarises the major findings from the implemented storage facilities. This review reports the state-of-the art of these TES and offers future perspectives based on 31 locations in Europe with a total available storage volume of nearly 800, 000 m³, corresponding to a capacity of 56, 600 MWh in the case of optimised storage utilisation. Three construction types prove to be the most promising concepts: tank thermal energy storages, pit thermal energy storages, and water-gravel thermal energy storages. The characteristic technological elements such as filling, waterproofing, and thermal insulation are discussed in detail to highlight successes and failures, as well as to display the latest innovations and research trends. Novel materials substitute conventional, less efficient alternatives while innovative methodologies are shown to reduce the risk of failure and significantly improve storage performance. The main challenges on the way to global market maturity include avoidance of primarily defective waterproofing, mitigation of energy and exergy losses caused by long-term material fatigues, and reduction of the often substantial construction costs. Graphical abstract: Image 1 Highlights: Review of variants for water-based closed seasonal thermal energy storage (TES). Analysis of all construction elements of seasonal TES based on 31 systems in Europe. Definition of barriers to overcome for market maturity of the selected technologies. Revelation of innovative attempts to utilise overlooked potentials of presented TES.